2024
DOI: 10.3390/agronomy14010228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Proportions of Organic Fertilizer Replacing Chemical Fertilizer on Soil Nutrients and Fertilizer Utilization in Gray Desert Soil

Weidan Lu,
Zhiqiang Hao,
Xiaolong Ma
et al.

Abstract: Organic fertilizer can improve soil management and alleviate soil nutrient loss caused by excessive fertilization. This study determines a fertilization scheme that can achieve high and stable crop yield and effective soil fertilization by exploring the effects of different organic fertilizer proportions on soil nutrient content, fertilizer utilization rate, and wheat yield. The experiment was conducted from 2018 to 2020 using the Xinchun 38 wheat variety and gray desert soil. The experiment used six treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Chemical fertilizer substitution with organic fertilizer may adjust the C and N ratio in agricultural soils [43] and lead to better synchronization of crop N demand and N input, thus improving N fertilizer utilization efficiency and alleviating N losses [44]. The application of organic fertilizers could elevate the SOC due to the adequate contact between soil organic materials, microbes, and enzymes accelerating the organic matter decomposition [45][46][47]. Our study found that OS at all ratios could increase the SOC in 2017, but the SOC contents in high organic substitution ratio treatments (60%, 100%, and 200%) were found to be lower than in the low OS and NOS treatments in 2018.…”
Section: Organic Substitution Improved Soil Quality In Apple Orchardsmentioning
confidence: 99%
“…Chemical fertilizer substitution with organic fertilizer may adjust the C and N ratio in agricultural soils [43] and lead to better synchronization of crop N demand and N input, thus improving N fertilizer utilization efficiency and alleviating N losses [44]. The application of organic fertilizers could elevate the SOC due to the adequate contact between soil organic materials, microbes, and enzymes accelerating the organic matter decomposition [45][46][47]. Our study found that OS at all ratios could increase the SOC in 2017, but the SOC contents in high organic substitution ratio treatments (60%, 100%, and 200%) were found to be lower than in the low OS and NOS treatments in 2018.…”
Section: Organic Substitution Improved Soil Quality In Apple Orchardsmentioning
confidence: 99%
“…The formation of grain quantity is due to having a higher phosphorus content, which is lower during yield formation. Different P fertilizer properties influenced wheat and maize spike numbers, 1000-grain weight, and nutrient absorption capacity, collectively impacting yield variations [43].…”
Section: Mechanism Of Different P Fertilizers On Increasing Crop Yieldmentioning
confidence: 99%
“…Available P was extracted with 0.5 mol/L NaHCO 3 and determined by UV-vis spectrophotometry (Olsen and Sommers, 1982). Available K was extracted with 1 mol/L ammonium acetate and determined by flame photometry (Lu et al, 2024). Soil Ca 2+ concentration was determined by inductively coupled plasma atomic emission spectrometry (Agilent ICP 720-OES, Varian Inc., Darmstadt, Germany) (Dahlquist and Knoll, 1978).…”
Section: Soil and Plant Sampling And Analysesmentioning
confidence: 99%